How to Force Polymer Gels to Show Volume Phase Transitions - Dušková-Smrčková, Miroslava; Dušek, Karel (ACS macro letters, 2019)
Relatively few polymer gels are known to show volume phase transition where the gels undergo an abrupt change in the degree of swelling by passing through a three-phase equilibrium. Characteristic for such transition is the existence of van der Waals (vdW) loop on the dependence of solvent chemical potential versus polymer concentration. For the χ-induced transition, the existence of vdW loop is determined by the concentration dependence of the interaction function. It is shown that expansive mechanical strains can assist in development of the vdW loop. Systems characterized by continuous change of the degree of swelling transform upon such strain into ones where the degree of swelling changes much and abruptly. Also, expansive modes of strain can make the transition wider and more robust in gels where transition is already observed under free swelling condition. The possibility to induce the volume phase transition by external stresses can be utilized for finding other stimuli sensitive gels, strengthening of gel response, and in modeling of properties of gel constructs by Finite Element Method.